(untitled) (Global Journals of Research in Engineering, 2022)
AURA users body composition results are used to provide information regarding the position of individual user s among the population for example if he she has lower or higher body fat ratio or muscle mass than others The comparison with other users is good for extra motivation since it creates a competitive element of training or and diet